2013
DOI: 10.1007/s10750-013-1590-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive scallop mariculture on macrobenthic assemblages in Sishili Bay, the northern Yellow Sea of China

Abstract: To elucidate the effects of scallop mariculture on the macrobenthic community in a moderate energy system, bimonthly samples from four transects along a distance gradient in Sishili Bay, the northern Yellow Sea of China, were investigated. Differences in macrobenthic community structure along the distance gradient were evaluated using univariate and multivariate analyses. The AZTI's Marine Biotic Index (AMBI) and multivariate-AMBI analyses indicated that the macrobenthic community suffered little disturbance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…When downward diffusion of oxygen and upward release of CO 2 are hampered by the pycnocline, a coupled trend of bottom oxygen depletion and acidification will occur (Zhai et al, 2012), making much worse the negative effects on coastal ecosystems (Mostofa et al, 2016). These changes are likely to be the greatest in the aquaculture area because of increasing nutrient loadings (Li et al, 2016(Li et al, , 2017 and decreasing water exchange rate (Gao et al, 2011;Han et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…When downward diffusion of oxygen and upward release of CO 2 are hampered by the pycnocline, a coupled trend of bottom oxygen depletion and acidification will occur (Zhai et al, 2012), making much worse the negative effects on coastal ecosystems (Mostofa et al, 2016). These changes are likely to be the greatest in the aquaculture area because of increasing nutrient loadings (Li et al, 2016(Li et al, , 2017 and decreasing water exchange rate (Gao et al, 2011;Han et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant polychaete L. latreilli is a very common carnivore in the northern Yellow Sea and the Bohai Sea. They construct semi-permanent burrows, from which they selectively feed upon small particles of subsurface deposits, microfauna, meiofauna and macrofauna (Watson et al ., 1984; Petch, 1986; Renaud et al ., 2007; MacDonald et al ., 2010; Han et al ., 2013). The worm L. latreilli was unrelated to TOC and not susceptible to the organic matter content (Han et al ., 2013), but it was significantly positively correlated to the content of coarse silt ( P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the polychaete community and the feeding guilds exhibited significant spatial and temporal differences. This conclusion coincided with the previous study derived from the analysis of the macrobenthic community that macrobenthic communities can be significantly affected by the sampling months and transects (Han et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Research in China has shown that suspended aquaculture systems can cause changes to surrounding ecological communities by significantly altering benthic, microbial, planktonic, and fish community dynamics (e.g., Jiang et al 2012;Han et al 2013a;Lu et al 2015;Zhao et al 2016).…”
Section: Ecological Impactsmentioning
confidence: 99%